MODEL OF JUDGES SUPERVISION FOR INDONESIA INDEPENDENT JUDICIAL POWER IMPLEMENTATION - Muhammad Fauzan; Riris Ardhanariswari; Ahmad Komari (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Judges supervision in Indonesia’s constitutional system in the future will only be performed by Judicial Commission. Judicial Commission involves Judicial Commission, Provincial Judicial Commission and District/City Judicial Commission based on each authority. The research discusses model of judges supervision to implement an independent judicial power for the future Indonesia. This research is a normative juridical research with statute approach and conceptual approach. The results show Local Judicial Commission has duties and authorities to; First, monitor and surpervise Judges’ behavior. Second, receive report from the people related to the violence of Ethic Code and/or Judges Code of Conduct. Third, verify, clarrify, ad investigate report related to presumption of violation of Ethic Code and/or Judges Code of Conduct covertly. Fourth, take legal action and/or other actions to individual, group or legal entity that degrade the honor and dignity of Judges.Keywords: Judicial Commission, judicial power, supervision